Cultural Value Orientations and Alcohol Consumption in 74 Countries: A Societal-Level Analysis - Inman, Richard A.; da Silva, Sara M. G.; Bayoumi, Rasha R.; Hanel, Paul H. P. (Frontiers in Psychology, 2017)
A significant proportion of all deaths globally can be attributed to alcohol consumption. Although a range of correlates of alcohol consumption have already been identified at the individual level, less is understood about correlates at the macro level, such as cultural values. As a development in this understanding may prove useful for global health organizations aiming to tackle the problems associated with excessive drinking, our aim was to investigate the association between encultured alcohol consumption and Cultural Value Orientations. We obtained data describing average alcohol consumption and Cultural Value Orientations, for 74 countries, from an online data repository. To assess whether Cultural Value Orientations are associated with alcohol consumption we calculated partial correlations and performed a ridge regression analysis. Our analyses revealed that Cultural Value Orientations were significantly associated with alcohol consumption, even after controlling for average income and education level. A profile emerged in which values of autonomy and harmony were shown to be positively associated with alcohol consumption, and hierarchy and embeddedness negatively associated with alcohol consumption. The effect was modified by gender. Changes in cultural Harmony, Mastery, Autonomy and Egalitarianism were associated with increases in alcohol consumption in males, but not females, while changes in cultural Embeddedness and Hierarchy were associated with decreases in consumption in females, but no change in males. Finally, we demonstrate that latitude, and by extension its covariates such as climatic demands, partially accounted for the effect of harmony and affective autonomy on alcohol consumption. This research highlights that cultural values, and their interaction with gender, should be an important consideration for international public health organizations aiming to tackle the problems associated with alcohol consumption, but that future research is required to fully understand the link between cultural values and alcohol.